Assessing Correlation of Residency Applicants' Interview Dates With Likelihood of Matching. Issue 2 (February 2018) - Avasarala, Sameer; Thompson, Elizabeth; Whitehouse, Sarah; Drake, Sean
Abstract : Objectives: This study aimed to determine whether the timing of an interview relative to the recruitment season was associated with being ranked or matched at an academic medical center. Methods: Eleven specialties (anesthesiology, diagnostic radiology, emergency medicine, family medicine, general surgery, internal medicine, neurology, neurosurgery, obstetrics-gynecology, orthopedic surgery, and psychiatry) that participated in the National Resident Matching Program were included in the study. Each program's total number of interview days during the October 2014–January 2015 interview season were divided equally into three interview time periods. The Cochran-Armitage trend test was used to evaluate associations among the three interview time periods (early, middle, and late) and interviewee outcomes (ranked or matched at our institution) for all subjects combined for each of the 11 programs and for specialty groups (medical, surgical, and hospital). Results: Of 1034 applicants included in the analyses, 60% were men. Most were graduated from US medical schools (59.8%; a total of 103 applicants obtained first-year training positions through the Match [95.4% combined fill rate]). Twenty-nine interviewed early, 38 in the middle, and 36 in the late period ( P = 0.3877). A total of 864 applicants were ranked by 1 of the 11 residency programs at the study site: 267 in the early period, 319 in the middle, and 278 in the late period ( P = 0.4184). Being ranked in association with specialty classification also showed no significant differences. Conclusions: Interview timing had no relation to the likelihood of a match or being ranked by 1 of the 11 programs studied at our institution. These findings help dispel misconceptions about the importance of the interview date for a successful match. Abstract : The Main Residency Match is a daunting process that thousands of applicants endure to obtain graduate medical education in the United States. The importance of the timing of an applicant's interview in relation to the recruitment season has always been a topic of discussion. Previous literature has shown that this perspective appears to be unfounded for internal medicine. This article evaluated the misconception among 10 other specialties that participate in the Main Residency Match.